Bedhaya Bedhah Madiun dance as a tourism superior asset in puro Mangkunagaran (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
This research aims to describe responds and cultural practice that happened in Mangkunagaran based on the repression of tourism world. This research is an analytical research based on ethnographic study. Triangulation data is collected from the interviewees together with the manuscript of dance performance and direct observation of Bedhaya Bedhah Madiun dance. Classification of tourism dance is responded by Puro Mangkunagaran as the objectification of Bedaya Bedhah Madiun as a free dance. The cultural response potentially alters the semiotic sign system associated with ‘bedhaya’ sign. This is a sign to Bedhaya to add the profanity of Bedaya as a tourist attraction. The objectivity of Bedhaya Bedhah Madiun by Puro Mangkunegara also has a potency to deconstruct the understanding of Bedhaya Bedhah Madiun as a tourist attraction, Bedhaya Bedhah Madiun is not an imitation from the origin and it is not full of variation. Cheap or expensive the dance is, becomes relative. Furthermore, secrecy does not exist in the stage reality, but moves to hyper reality (in the fantasy and nostalgia of the audience). Respond and cultural practice of indicated Puro Mangkunagaran as a cultural institution which is active in doing the production-reproduction of meaning and the tourism enhancement.